Root-centered sodium sequestration and transcriptomic regulation under salt and alkali stress in wild soybean (Glycine soja) - Wang, Meng; Qu, Yingyu; Lu, Xueli; Gillani, Syeda Wajeeha; Song, Yiru; Bai, Yu; Li, Yiqiang; Zhang, Chengsheng; Xu, Zongchang; Meng, Chen (Frontiers in Plant Science, 2025)
Salt and alkali stress are major constraints on soybean productivity, but their distinct impacts during early development remain insufficiently understood. Wild soybean (Glycine soja), a valuable genetic resource for stress tolerance, was evaluated under salt (0.6% and 1.2% NaCl) and alkali (pH 9.16) stress by assessing germination, seedling traits, ion accumulation, and transcriptomic responses. Salt stress permitted partial germination, whereas alkali stress completely suppressed radicle emergence. Seedling growth and height showed tolerance under salinity, but high pH caused severe wilting and mortality. Ion profiling revealed root Na+ sequestration with stem K+ buffering in salinity, whereas alkali stress confined Na+ to roots, maintaining the highest stem K+/Na+ ratio. Bioaccumulation and translocation factors peaked at 0.6% NaCl in wild soybean. Transcriptome analysis identified 7,355 DEGs grouped into five clusters, enriched in phenylpropanoid/flavonoid biosynthesis and hormone signaling. Salt stress upregulated genes including FLS, F3H, and F3′5′H, whereas alkali stress induced CHS, peroxidase, and CYP75B1. Ion transport regulation differed, with HKT1 and KT11 activated under salinity and NIP5–1 under alkalinity. Among 385 TF-related DEGs, MYB, ERF, bHLH, and WRKY dominated (67% of total), with complex TF-gene networks observed under salt stress. Exogenous flavonoids (rutin, eriodictyol) treatment enhanced leaf area, root length, and plant height under salt and alkali stress treatments. These results suggest that G. soja mitigates ion toxicity via root Na+ sequestration, stress-responsive gene regulation, and flavonoid-mediated growth enhancement, providing insights into adaptive mechanisms under salt and alkali stress.